Pengaruh Stres Kerja terhadap Kinerja Karyawan (Studi Kasus pada Toyota Nasmoco Surakarta) - Maulida, Diana; , Jati Waskito S.E., M.Si (2015)
This research aims analyzing the effect of stressors that including environment of work stressor, individual stressor, and organizational stressor to employee performance of Toyota Nasmoco Surakarta, and determines the significant influence between three stressors to employee performance of Toyota Nasmoco Surakarta. The sampling technique used simple random sampling method, where every population member has an opportunity to be chosen as sampel member. Counted amout 78 people from 120 total populate people., and data testing techniques used in this research include test validity, reliability test with Alpha Cronbach. The classic assumption test, multiple linear regression analysis, t test to test and prove the research hypothesis. Data collection methods used were questionnaires, interviews, and documentation. Data were analyzed with multiple linear regression using statistical software of SPSS 16.0 for windows. Results showed that enviromental stressor, individual stressor, organizational stressor factors influence to employee's job performance at Toyota Nasmoco Surakarta as high as 7,2%, simulataneously and the one with the most partially significant influence toward employee's job performance is individual stressor factor with 51,9%.